Computational fluid dynamics modeling of a low pressure cold spraying nozzle - Canales, H.; Lytvynov, A. A.; Markovich, S. E.; Dolmatov, A. I. (НТУ "ХПІ", 2014)
The fluid dynamics design and optimization is one of the most important tasks in order to improve the Cold Spraying process. In the present study the Computational Fluid Dynamics methodology is applied in order to study the fluid dynamic characteristics of the supersonic airflow through the SK-20 Low Pressure Cold Spraying nozzle attached to a Dymet 405 Cold spraying system. A particle study was performed in order to determine the particle velocity and temperature of several powder materials commercially available. In order to validate the calculations, the results from the Computational Fluid Dynamics methodology are corroborated with experimentation using a supersonic pitot tube that measures the static and dynamic pressure from which Mach number at the exhaust of the nozzle is determined. In this study, it is found that the experimental data agrees well with the results obtained from the Computational Fluid Dynamics methodology.

Розробка і оптимізація гідродинаміки сопла є одним з найбільш важливих завдань для того, щоб поліпшити процес холодного напилення. У цьому дослідженні обчислювальна методика Fluid Dynamics яка застосовується для того, що б вивчити динамічні характеристики рідини надзвукового повітряного потоку через сопло SK-20 системи холодного напилення низького тиску, що входить до складу системи ДІМЕТ 405. Дослідження частинок були виконані для того, щоб визначити швидкість частинок і температуру в декількох поширених порошкових матеріалів. Для підтвердження розрахунків методології Fluid Dynamics, були виконані експерименти з використанням надзвуковий трубки Піто, що вимірює статичний і динамічний тиску, від яких визначається число Маха на вихлопі сопла. У цьому дослідженні було виявлено, що експериментальні дані добре узгоджуються з результатами, отриманими з обчислювальної методології Fluid Dynamics.
Обчислювальне моделювання гідродинаміки сопла холодного напилення низького тиску